BEYOND BORDERS: WHAT IS STOPPING UZBEKS FROM TRAVELING THE WORLD? (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Although tourism activity is growing globally and travel information has become more accessible, a significant portion of the population of Uzbekistan remains on the sidelines of this trend. This article analyzes the main reasons for the low level of participation of Uzbeks in international tourism.